HAK KEWARISAN ZAWIL ARHAM (PERSPEKTIF MAZHAB HANAFIYAH DAN SYAFI’IYAH) - Sofia Adela (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2018)
In this life, humans have their own property in their lifetime, but after the man passes away, the property will belong to his heirs. The jurists agree that ashabul Furud is prioritized in taking inheritance, if there is a remnant, it is given for heirs of asabah. The jurists also agree that if someone dies and has the heirs of ashabul furudh or asabah, the relatives of the zawil arham will not have right to inherit. They have differents arguments about who will has the right to inherit, if the heir does not leave ashabul furudh or ashabah relatives. The Hanafiyah School argues that the zawil arham group has the right to inherit, if the heir does not leave ashabul furudh relatives and asabah. On the other hand, the Syafi'iyah school argues that the zawil arham group does not have right to inherit, but the property should be given to the Baitul Mal. The results of the study concluded that according to the Hanafiyah School, zawil arham is more rightful to get inheritance than others, because they have a kinship relationship with the heir, and they are more prioritized than baitul mall. Otherwise, the school of Syafi'yah stated that zawil arham does not have right to inherit the property from the heir because zawil arham is not classified as relatives of ashabul furudh or asabah, so that the property must be handed to baitul mal. The Legal terms used by the Hanafiyah school is based on the Koran in Surah al-Anfal (75), and hadith. Meanwhile, the Shafi'iyah school is based on Surah maryam (64), and hadith.